1993
DOI: 10.1152/ajpgi.1993.265.2.g270
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic regulation of guinea pig duodenal bicarbonate secretion

Abstract: Although it is well known that vagal stimulation induces duodenal HCO3- secretion, there is presently no information about the nature of the cholinoceptor and the intracellular signals involved. In a series of experiments performed in a guinea pig duodenal loop model in situ, intravenous carbachol, atropine, pirenzepine, and hexamethonium were used to determine the extent of cholinergic stimulation and the types of cholinoceptors. Carbachol (2 micrograms.kg-1.5 min-1) stimulated HCO3- secretion threefold, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…Several studies have shown that the nonselective muscarinic antagonist atropine inhibits the stimulation of muscosal HCO 3 Ϫ secretion by carbachol in rats (23,33) and guinea pigs (29) in vivo, as well as in rabbit duodenal mucosa in vitro (15). In our study, atropine abolished carbachol-induced increases in mouse duodenal mucosal I sc and HCO 3 Ϫ secretion, suggesting that these are specific responses likely occurring via stimulation of muscarinic receptors on mouse duodenocytes. ]…”
Section: It Is Generally Accepted That Epithelial Hcosupporting
confidence: 62%
“…Several studies have shown that the nonselective muscarinic antagonist atropine inhibits the stimulation of muscosal HCO 3 Ϫ secretion by carbachol in rats (23,33) and guinea pigs (29) in vivo, as well as in rabbit duodenal mucosa in vitro (15). In our study, atropine abolished carbachol-induced increases in mouse duodenal mucosal I sc and HCO 3 Ϫ secretion, suggesting that these are specific responses likely occurring via stimulation of muscarinic receptors on mouse duodenocytes. ]…”
Section: It Is Generally Accepted That Epithelial Hcosupporting
confidence: 62%
“…Vasoactive intestinal polypeptide (VIP) is the most likely humoral factor mediating the HCO 3 -secretory response to acid, because it is a potent stimulant of duodenal HCO 3 -secretion and is released from nerve endings during the exposure of duodenal mucosa to acid [17] . Odes et al [32] reported that acetylcholine increases a release of VIP from enteric nerves via both muscarinic M 1 and M 3 receptors, which in turn stimulates HCO 3 -secretion in the duodenum. Since nizatidine significantly potentiated the HCO 3 -response to acetylcholine, it is possible that the acid-induced HCO 3 -secretion is also enhanced by the anti-AChE activity in the presence of nizatidine.…”
Section: Figurementioning
confidence: 99%
“…A variety of substances, including prostaglandin (PG) E 2 (PGE 2 ), vasoactive intestinal peptide and theophyline, have been shown to stimulate the HCO – 3 secretion in both in vivo and in vitro [3, 4, 5, 6]. These agents increase intracellular levels of adenosine-3′,5′-cyclic monophosphate (cAMP) by stimulating the adenylate cyclase or inhibiting the phosphodiesterase [6], suggesting that cAMP has a mediator role in duodenal HCO – 3 secretion.…”
Section: Introductionmentioning
confidence: 99%